Sanitation And Temperature Factors Related To Existence Of Cockroach And Rats Vectors On Passenger Ship In Kendari City Port: Cockroach And Rats Vectors - Eka Dharma Marhanto; Anry Hariadhin Depu (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Objectives: Ship arrival and departure activities have an important influence on the transmission of various vectors which have the potential to infect the ship's crew and passengers. This study aims to determine the factors associated with the presence of vectors on passenger ships. Methods: This type of research is observational. The population is a local passenger ship that anchors at 4 ports in Kendari City, with a population of 44 ships and a sample of 40 ships.with the sampling technique is systematic random sampling. Results: The results of the study used the Chi Square test between sanitary conditions and the presence of cockroaches (15.708>3.841), there was a relationship between sanitary conditions and the presence of rats (14.249>3.841), there was a relationship between temperature and the presence of cockroaches (9.724>3.841), there was a relationship between temperature and the presence of rats (7.901>3.841). Conclusion: There were relationship between sanitary conditions and temperature with the presence of cockroach and rat vectors on passenger ships mooring at the Port of Kendari City. Therefore it is necessary to increase the sanitary conditions and temperature in the room.